Pengaruh Sifat Machiavellian, Komitmen Profesional, dan Tingkat Keseriusan Kecurangan terhadap Niat Melakukan Whistleblowing - Yolla Yelman Liani; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to analyze the effect of Machiavellian traits, professional commitment, and the seriousness of fraud on the intention to commit whistleblowing. This research is a causality associative research with a quantitative approach. The population in this study were all employees at BPKD, BAPPEDA, BKPSDM, DPMPTSP in South Solok Regency. The data collection method uses questionnaires which are distributed directly. The data used in this research is primary data. The hypothesis in this study was tested using multiple regression analysis. The results of this study indicate that Machiavellian traits have no effect on whistleblowing intentions, professional commitment and the seriousness of fraud have a positive and significant effect on whistleblowing intentions.